2021
DOI: 10.3390/ijerph18062828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Classroom Active Desks on Children and Adolescents’ Physical Activity, Sedentary Behavior, Academic Achievements and Overall Health: A Systematic Review

Abstract: The purpose of this systematic review was to examine the effects of active desks in the school setting on sedentary behavior, physical activity, academic achievements and overall health among children and adolescents aged 5–17 years. A systematic literature search was conducted using five databases until October 2020. Twenty-three studies were included. Studies reported an increase of around 36% in energy expenditure for cycling desks and between 15% and 27.7% for upright active desks. Children increased inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 65 publications
0
22
0
5
Order By: Relevance
“…Therefore, for this age group we recommend interventions taking this approach. Regarding physical environment interventions, we propose creating a movement-friendly environment, e.g., through the provision of height adjustable desks in schools [ 101 , 102 ]. When implementing social environment interventions, a focus should be placed on active involvement of the family [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for this age group we recommend interventions taking this approach. Regarding physical environment interventions, we propose creating a movement-friendly environment, e.g., through the provision of height adjustable desks in schools [ 101 , 102 ]. When implementing social environment interventions, a focus should be placed on active involvement of the family [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, these reviews have only examined experimental study designs. Some reviews examined any school-related intervention [ 19 , 23 ], while the others were specific to recess [ 25 ], classrooms [ 22 , 26 ], or standing desks in particular [ 20 , 21 , 24 ]. The two reviews that examined any school-related interventions were specific to adiposity indicators in primary school-aged children [ 23 ], and physical activity in older adolescents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two reviews that examined any school-related interventions were specific to adiposity indicators in primary school-aged children [ 23 ], and physical activity in older adolescents [ 19 ]. Further, of the reviews examining a broad spectrum of health and well-being indicators, two were specific to standing desk interventions [ 20 , 24 ] and the other was specific to recess [ 25 ]. Collectively, these reviews have not provided an up-to-date and exhaustive overview of the associations between school-related sedentary behaviours and health and well-being indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Sit–stand desks, when incorporated into the classroom environment, have shown potential for breaking up and reducing children’s sitting time and increasing movement. To date though, most studies within this area have been limited to quasi-experimental or crossover trials with relatively short intervention periods (e.g., <12 weeks) or small-scale single-school pilot studies [ 29 , 30 , 31 , 32 ]. Recent studies from a range of countries have supported these earlier findings and demonstrated that sit–stand desks within the classroom leads to beneficial changes (reductions) in children’s class/school-time spent sitting [ 33 , 34 , 35 , 36 , 37 ] or total daily time spent sedentary [ 19 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%